Auctions and fair division games under different price rules: Individual bid functions, prices and efficiency rates - Werner Güth; Radosveta Ivanova-Stenzel; Manfred Königstein; Martin Strobel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
In auctions an outside seIler offers a commodity for sale and collects the revenue w hich is achieved. In fair division games the object is owned by the group of bidders. Consequently the auction's revenue is equally distributed among all bidders. In our experiment participants face four auction types (first versus second price - auction versus fair division game) repeteadly. Due to the strategy method (one bids before learning one's private value) we can investigate the slope and curvature of individual bid functions) the evidence for risk aversion, the comparative statics with respect to the game type, the price expectations and the efficiency rates.
urn:nbn:de:kobv:11-10046888
Keywords: D44; C91; 330; auctions; fair division games; bid function